Local English testing in China's tertiary education: Contexts, policies, and practices. (July 2022) - Fan, Jason; Frost, Kellie; Jin, Yan
Accompanying the still pervasive influence of the College English Test (CET), some universities in China, especially the higher-ranking ones, have in recent years devised and implemented their own local English testing regimes. This significant shift, however, has captured limited research attention. Building on considerations in local language testing and adopting a broad view of language tests as embedded within policy spaces, we examined the policy and curricular contexts surrounding the introduction of local testing regimes, the local testing practices that emerged from these contexts, and stakeholders' reactions to changes in local testing practices at China's universities. Data were collected through in-depth, semi-structured interviews with local testing project coordinators from five prominent universities in China. Our findings revealed two contrasting approaches to local testing, each implemented to promote productive English skills, widely associated with university-level internationalisation efforts, and to better align assessment practices with university-specific student cohorts and College English (CE) teaching programmes. Each local testing regime was characterised by different processes of test development and implementation, and its tensions and challenges. This study provides important insights into the situated nature of local testing policies and practices in Chinese universities, highlighting the affordances and constraints offered by different approaches to local testing.